Obstructed labor as an underlying cause of maternal mortality in Kalukembe, Angola, 2017 - Priscila R Cummings; Daniel B Cummings; Kathryn H Jacobsen (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background The goal of this study was to examine the primary and contributing causes of maternal mortality in Angola. # Methods This retrospective case series was conducted at Kalukembe IESA Mission Hospital, Huila province, Angola, southwestern Africa. We reviewed the charts of all 865 deliveries at the hospital and all women admitted for postnatal care after delivery in 2017. # Results The primary classifications for the 18 pregnancy-related fatalities were hemorrhage or anemia (n=5), sepsis and other maternal infections (n=5), hypertensive disorders (n=4), uterine rupture (n=2), and metastatic gestational trophoblastic neoplasia (n=2). Obstructed labor was a major contributor to seven of the 18 fatalities, including three anemia cases, one sepsis case, and one eclampsia case. Five of the seven gave birth outside the hospital. None of the seven had a live birth. # Conclusions Obstructed labor remains a common obstetric complication leading to maternal death in low-income countries, but it is often hidden in statistics that focus solely on the most immediate causes of death. Current estimates of the global burden of maternal mortality may significantly undervalue the preventable burden from obstructed labor and the need for increased investment in interventions to address it.